Structure of yeast U6 snRNPs: Arrangement of Prp24p and the LSm complex as revealed by electron microscopy - Karaduman, Ramazan (Cold Spring Harbor Laboratory Press, 2008)
Protein components of the U6 snRNP (Prp24p and LSm2–8) are thought to act cooperatively in facilitating the annealing of U6 and U4 snRNAs during U4/U6 di-snRNP formation. To learn more about the spatial arrangement of these proteins in S. cerevisiae U6 snRNPs, we investigated the structure of this particle by electron microscopy. U6 snRNPs, purified by affinity chromatography and gradient centrifugation, and then immediately adsorbed to the carbon film support, revealed an open form in which the Prp24 protein and the ring formed by the LSm proteins were visible as two separate morphological domains, while particles stabilized by chemical cross-linking in solution under mild conditions before binding to the carbon film exhibited a compact form, with the two domains in close proximity to one another. In the open form, individual LSm proteins were located by a novel approach employing C-terminal genetic tagging of the LSm proteins with yECitrine. These studies show the Prp24 protein at defined distances from each subunit of the LSm ring, which in turn suggests that the LSm ring is positioned in a consistent manner on the U6 RNA. Furthermore, in agreement with the EM observations, UV cross-linking revealed U6 RNA in contact with the LSm2 protein at the interface between Prp24p and the LSm ring. Further, LSmp–Prp24p interactions may be restricted to the closed form, which appears to represent the solution structure of the U6 snRNP particle.